An Electrochemically and Thermally Switchable Donor–Acceptor [c2]Daisy Chain Rotaxane1. (21st January 2014) - Bruns, Carson J.; Li, Jianing; Frasconi, Marco; Schneebeli, Severin T.; Iehl, Julien; Jacquot de Rouville, Henri‐Pierre; Stupp, Samuel I.; Voth, Gregory A.; Stoddart, J. Fraser
Abstract Although motor proteins are essential cellular components that carry out biological processes by converting chemical energy into mechanical motion, their functions have been difficult to mimic in artificial synthetic systems. Daisy chains are a class of rotaxanes which have been targeted to serve as artificial molecular machines because their mechanically interlocked architectures enable them to contract and expand linearly, in a manner that is reminiscent of the sarcomeres of muscle tissue. The scope of external stimuli that can be used to control the musclelike motions of daisy chains remains limited, however, because of the narrow range of supramolecular motifs that have been utilized in their templated synthesis. Reported herein is a cyclic daisy chain dimer based on π‐associated donor–acceptor interactions, which can be actuated with either thermal or electrochemical stimuli. Molecular dynamics simulations have shown the daisy chain's mechanism of extension/contraction in the ground state in atomistic detail.